STRUCTURAL DESIGN OF A WORKBENCH FOR THE NEEDS OF A SERVICE TECHNICIAN - Denis Molnár; Miroslav Blatnický; Ján Dižo; Jozef Harušinec; Rastislav Maliňák (Perner’s Contacts, 2023)
The presented paper deals with the structural design of a workbench with adjustable height, which will serve as part of the equipment of a light commercial vehicle for the needs of a service technician. The main objective of this paper is to create a functional design and 3D CAD model of a workbench that will meet the requirements of safety, mobility, and simple utilisation. Moreover, the design needs to consider the requirements of adjustable height and the dimensions of the work vehicle. The lifting mechanism is represented by arms fitted with sleeves that move along a lead trapezoidal screw rotating by a hand crank. In this paper, the force action in the axis of the threaded rod of the lifting mechanism is scrutinised in two extreme positions (highest and lowest position). The highest axial load on the threaded rod was found to be 9927.13 N in the lowest position of the mechanism. On the basis of this load, a right and left-hand trapezoidal threaded rod TR16×4 is selected, which satisfied the strength condition. The design of the sleeve height and the number of sleeve threads required are essential for safe utilisation. Due to the dimension of the guide rod, the height of the sleeve is selected to be 40 millimetres. The work surface is an important part of the workbench and consists of two parts. The chief larger part is made of medium density fibreboard and the smaller modular part can be in the two modular forms. The first version is the medium density fibreboard, and second alternative is a board designed to fix the components during their maintenance, repair as well as for welding.